Two new species of Cosmocercidae (Nematoda: Cosmocercoidea) of Leptodactylus macrosternum Miranda-Ribeiro (Anura: Leptodactylidae) from Caatinga Biome, Brazil - Felix-Nascimento, Gabriela; Vieira, Fabiano Matos; Muniz-Pereira, Luís Cláudio; Moura, Geraldo Jorge Barbosa De; Ribeiro, Leonardo Barros; Oliveira, Jaqueline Bianque De (Zootaxa, 2020)
In the current study, two new species of Cosmocercidae nematodes parasitizing the anuran Leptodactylus macrosternum (Leptodactylidae) from two localities in the municipality of Petrolina, sub-middle São Francisco river, state of Pernambuco, Brazil, were described. Oxysomatium petrolinensis n. sp. differs from all congeneric species for having the male caudal papillae distribution pattern unique in this genus, in which the last three pairs of pre-cloacal papillae are located lateroventrally on the anterior border of the cloacal aperture. Additionally, the new species has an unpaired medial precloacal papilla, seven pairs of postcloacal papillae, and a relatively unique spicule size. Oxyascaris caatingae n. sp. differs from all congeneric species mainly for having males with a medial unpaired precloacal papilla and a distribution pattern of caudal papillae unique to this species, being the only species of the genus with adcloacal papillae. The current study proposes the description of Oxysomatium petrolinensis n. sp., fourth species and the first report of this genus in hosts from the Neotropical region. In addition, it describes Oxyascaris caatingae n. sp., which is the fifth species of the genus.